Hypermedia interactive avenues of information ([Corvalles, Or.] Oregon State University, 1989)
A free form discussion with a live panel of noteworthy hypermedia practitioners. Deals with the retrieval of information through interactive computer system.
VHS.
Moderator, Rob Philips.
Keywords: Hypermedia systems; Interactive computer systems; Computer